Methodological Analysis Of Tafsîr Fî Zhilâl Al-Qur'ân: Between Reflective Approach And Epistemological Criticism - Ariyadri, Acep; Anggriyani, Anggriyani (PT. Student Rihlah Indonesia, 2025)
Fî Zhilâl Al-Qur'ân by Sayyid Qutb is one of the most influential works in the field of contemporary Qur'an interpretation, offering a unique and reflective approach to understanding the Qur'ân. Instead of focusing on technical linguistic analysis or classical historical narratives, this work emphasizes the internalization of the spirit and message of the Qur'an. Qutb's reflective method highlights resistance to tyranny and promotes the establishment of divine values in socio-political life. However, this work is not immune to epistemological criticism, especially regarding the lack of scientific references, ideological subjectivity, and oversimplification of complex meanings. This paper aims to analyze the interpretive methodology used in Fî Zhilâl al-Qur'an, identify its strengths and weaknesses, and place it in a broader landscape of modern Qur'anic interpretation. Using a qualitative approach and content analysis, the study found that although this work lacks academic rigor in some respects, it significantly contributes to resurrecting the Qur'an's role as a dynamic and revolutionary guide to life.